(untitled) (CAHIERS MAGELLANES-NS, 2024)
The integration of artificial intelligence (AI) across organizational functions has emerged as a critical factor in enhancing performance and achieving strategic objectives. This research delves into the interdisciplinary applications of AI within Marketing, Human Resources (HR), and Finance, illustrating how AI technologies can be leveraged to optimize organizational outcomes. In Marketing, AI-driven predictive analytics enable precise targeting and segmentation, enhancing the efficacy of campaigns and personalization of customer interactions. Machine learning algorithms analyze consumer behavior, predict trends, and automate decision-making processes, thereby increasing marketing ROI and customer satisfaction. In the realm of HR, AI revolutionizes talent management by streamlining recruitment processes through intelligent screening and matching of candidates, reducing bias, and enhancing diversity. AI-powered analytics provide insights into employee performance and engagement, facilitating the development of tailored training programs and predictive attrition models. This data-driven approach enables HR professionals to foster a more dynamic and motivated workforce. Finance departments benefit significantly from AI applications in risk management, fraud detection, and financial planning. Advanced algorithms assess creditworthiness, identify fraudulent activities in real-time, and optimize investment portfolios. AI-driven financial forecasting and budgeting tools enhance decision-making accuracy, providing a competitive edge in financial management. This paper also addresses the ethical and practical challenges of AI implementation, such as data privacy concerns, the need for regulatory compliance, and the potential for job displacement. It underlines the importance of a cohesive strategy that aligns AI initiatives with organizational goals and culture. By synthesizing insights from multiple disciplines, this research offers a holistic view of AI's transformative potential. It provides a strategic framework for organizations aiming to harness AI to drive efficiency, innovation, and sustainable growth, ultimately achieving superior performance in an increasingly competitive business environment.